Can analyst coverage reduce corporate tax avoidance? Evidence from China - Xiaofei Shi; Yuanhao Shen; Yuanfang Wang; Jinlong Han (PLoS ONE, 2025)
Tax avoidance is a widespread problem, much explored in the literature. Using a sample of A-share listed companies in China from 2009 to 2021, this study finds that analyst coverage significantly inhibits corporate tax avoidance behavior, mainly by improving the information environment and alleviating agency problems. Further analysis finds that the role of analyst coverage is more significant in firms where investment in innovation is limited, state-owned enterprises, and those with low management shareholding. The paper enriches the relevant literatures about analyst coverage and corporate tax avoidance, identifies the potential to inhibit corporate tax avoidance from the perspective of information environment and agency costs and provides suggestions for regulators and corporate governance.